2020
DOI: 10.1155/2020/2854574
|View full text |Cite
|
Sign up to set email alerts
|

Differential Transform Algorithm for Functional Differential Equations with Time-Dependent Delays

Abstract: An algorithm using the differential transformation which is convenient for finding numerical solutions to initial value problems for functional differential equations is proposed in this paper. We focus on retarded equations with delays which in general are functions of the independent variable. The delayed differential equation is turned into an ordinary differential equation using the method of steps. The ordinary differential equation is transformed into a recurrence relation in one variable using the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…The main advantage of the DTM is that it can be applied directly to nonlinear differential equations without requiring linearization, discretization, or perturbation. As mentioned earlier the DTM has been extensively used to solve differential equations [14,15] (both ordinary and partial), delay differential equations [16], integral equations [19], integro-differential equations [20], and so on. In this section, we introduce some essential concepts of differential transform and apply them to solve the BEVP (36)-(39).…”
Section: Differential Transform Methods Of Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantage of the DTM is that it can be applied directly to nonlinear differential equations without requiring linearization, discretization, or perturbation. As mentioned earlier the DTM has been extensively used to solve differential equations [14,15] (both ordinary and partial), delay differential equations [16], integral equations [19], integro-differential equations [20], and so on. In this section, we introduce some essential concepts of differential transform and apply them to solve the BEVP (36)-(39).…”
Section: Differential Transform Methods Of Solutionmentioning
confidence: 99%
“…Numerical methods such as finite difference methods, shooting method, spectral methods, variational methods (Galerkin and Rayleigh-Ritz methods) and similar methods that handle boundary value problems can be used, with suitable modifications, to solve BEVPs (see Rees [1] and Barletta and Rees [2]). Likewise approximate analytical methods such as homotopy methods (homotopy analysis method -HAM [3][4][5], homotopy perturbation method -HPM [6][7][8]), variational iteration method (VIM) [9][10][11], Adomian decomposition method (ADM) [12,13], DTM [14][15][16] and many other methods may also be suitably altered to deal with BEVPs. So far the DTM has been successfully applied in solving initial and boundary value problems involving ordinary and partial differential equations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that DT is convenient for solving a variety of initial value problems (IVPs), covering the range from ordinary to functional, partial and fractional differential equations [23][24][25][26]. In particular, results on the differential equations with proportional, constant and non-constant delays can be found in [27][28][29].…”
Section: Differential Transformmentioning
confidence: 99%
“…It has applications in solving different types of problems for all classes of differential equations (ordinary, partial, delayed, fractional, fuzzy etc). The recent developments and applications of DTM are discussed in [15,[17][18][19] and references therein.…”
Section: Introductionmentioning
confidence: 99%